2009
DOI: 10.1590/s0102-311x2009001100015
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida de cinco anos e fatores prognósticos em coorte de pacientes com câncer de mama assistidas em Juiz de Fora, Minas Gerais, Brasil

Abstract: O objetivo deste estudo foi analisar a sobrevida de cinco anos e os fatores prognósticos em mulheres com câncer invasivo da mama, submetidas à cirurgia e assistidas em Juiz de Fora, Minas Gerais, Brasil, com diagnóstico da doença entre 1998 e 2000. As variáveis analisadas foram: idade, cor, local de residência, variáveis relacionadas ao tumor e ao tratamento. Foram estimadas as funções de sobrevida pelo método de Kaplan-Meier, e o modelo de riscos proporcionais de Cox foi utilizado para avaliação prognóstica. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
40

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 29 publications
(47 reference statements)
2
16
1
40
Order By: Relevance
“…However, it is important to note that mortality due to circulatory diseases can occur due to innumerable factors such as the age of women, the side effects of treatments or due to the presence of preexisting diseases. 14,23 The incidence of breast cancer was higher in patients aged 50-69 years, which is in agreement with the coverage of screening programs recommended by the Ministry of Health.…”
Section: Objectives Methodssupporting
confidence: 82%
“…However, it is important to note that mortality due to circulatory diseases can occur due to innumerable factors such as the age of women, the side effects of treatments or due to the presence of preexisting diseases. 14,23 The incidence of breast cancer was higher in patients aged 50-69 years, which is in agreement with the coverage of screening programs recommended by the Ministry of Health.…”
Section: Objectives Methodssupporting
confidence: 82%
“…O aumento da mortalidade por câncer de mama no município mineiro, onde recentes estudos em mulheres portadoras da doença mostraram sobrevida superior a 81% em cinco anos 25,26 , sugere aumento da incidência da doença na cidade.…”
Section: Resultsunclassified
“…More advanced stages of breast neoplasm are related to shorter DFS and overall survival. 11,[27][28][29] A survey of women with stage III breast cancer subject to the same kind of treatment showed a difference in DFS at 5 years between stage IIIA (84%) and IIIB (33%) patients. 30 In a study that compiled data from the EUROCARE and SEER trials, the risk of death was shown to increase alongside staging (T2-3N0M0: risk of 4.87; T1-3NM0: risk of 10.44; T4M0: risk of 17.22; all in relation to T1N0M0).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Early diagnosis associated with treatment could reduce the mortality of the disease. [8][9][10][11][12] Disease-free survival (DFS) is defined as the time between the beginning of the treatment and disease progression or death from any cause. [13][14][15] Factors related to a shorter DFS include tumors larger than 2 cm, the presence of lymph node involvement and more advanced stages of the disease.…”
Section: Introductionmentioning
confidence: 99%